Xenon difluoride dry etching for the microfabrication of solid microneedles as a potential strategy in transdermal drug delivery - Eş, I; Kafadenk, A; Gormus, MB; Inci, F (Wiley, 2023)
Although hypodermic needles are a "gold standard" for transdermal drug delivery (TDD), microneedle (MN)-mediated TDD denotes an unconventional approach in which drug compounds are delivered via micron-size needles. Herein, an isotropic XeF2 dry etching process is explored to fabricate silicon-based solid MNs. A photolithographic process, including mask writing, UV exposure, and dry etching with XeF2 is employed, and the MN fabrication is successfully customized by modifying the CAD designs, photolithographic process, and etching conditions. This study enables fabrication of a very dense MNs (up to 1452 MNs cm-2 ) with height varying between 80 and 300 µm. Geometrical features are also assessed using scanning electron microscopy (SEM) and 3D laser scanning microscope. Roughness of the MNs are improved from 0.71 to 0.35 µm after titanium and chromium coating. Mechanical failure test is conducted using dynamic mechanical analyzer to determine displacement and stress/strain values. The coated MNs are subjected to less displacement (≈15 µm) upon the applied force. COMSOL Multiphysics analysis indicates that MNs are safe to use in real-life applications with no fracture. This technique also enables the production of MNs with distinct shape and dimensions. The optimized process provides a wide range of solid MN types to be utilized for epidermis targeting.